Trading at Crossroad and the De/Re-territorialization of Borders: An Anthropological Review - สังขมณี, จักรกริช (Journal of Social Sciences, Chiang Mai University, 2019)
This article examines several academic works that are related to cross-border trade issues. The purpose of this article is to understand how trading space can generate anthropological perspectives with specific reference to re/de-territorialization issues. Through a literature review of authoritative works in cross-border trade, this article tackles on two main debates concerning the process of re/de-territorialization: 1) the demarcation between formal and informal forms of trading practices and 2) the intricate relationships between locality, nation-state, the emergence of economic region and the transformation of trading practices at international borders. Besides tracing these two debates, this article examines some of the seminal works on cross-border trade in the Mekong region. Toward the end, it raises some issues of border trade which warrant further investigation in understanding re/de-territorialization at the borders.